The role of chitosan in the future of regenerative endodontics. A narrative review - Leal Pavez, Jaime Ignacio (2021)
Abstract: Regenerative endodontics is based on the principles of tissue engineering: Stem Cells, Growth Factors and Scaffolds. The Scaffolds fulfill the function of support for cells. The most widely used for this purpose is the patient's own clot blood. A wide variety of scaffold types have been proposed, In the current literature, a scaffold based on chitosan nanoparticles is studied. It presents promising in vitro results due to its antimicrobial capacity and the possibility of a “controlled” release of the element, which is charged to the nanoparticle. By adapting these aspects, revascularization could improve your success rate. Faced with this possibility, it is essential to describe the role of chitosan and its combinations with other materials in endodontic regeneration procedures as scaffold. To conduct the research, the pubmed and Scopus databases were used as well as the specialized journals "Journal of Endodontics" and the "International Journal Endodontics". The limited literature indicates that in in vivo studies there is no statistically significant difference between the use of chitosan as a scaffold and the patient's blood clot. Chitosan alone does not improve the results in regenerative endodontics in non-vital teeth, this situation changes when it is associated with a growth factor (only evaluated in in vitro studies). Faced with this situation, it is necessary to carry out studies with improved formulas.